Modulation of α-enolase post-translational modifications by dengue virus: increased secretion of the basic isoforms in infected hepatic cells. - Luiza M Higa (Public Library of Science (PLoS), 2014)
Hepatic cells are major sites of dengue virus (DENV) replication and liver injury constitutes a characteristic of severe forms of dengue. The role of hepatic cells in dengue pathogenesis is not well established, but since hepatocytes are the major source of plasma proteins, changes in protein secretion by these cells during infection might contribute to disease progression. Previously, we showed that DENV infection alters the secretion pattern of hepatic HepG2 cells, with α-enolase appearing as one of the major proteins secreted in higher levels by infected cells. ELISA analysis demonstrated that DENV infection modulates α-enolase secretion in HepG2 cells in a dose-dependent manner, but has no effect on its gene expression and on the intracellular content of the protein as assessed by PCR and western blot analyses, respectively. Two-dimensional western blots showed that both intracellular and secreted forms of α-enolase appear as five spots, revealing α-enolase isoforms with similar molecular weights but distinct isoeletric points. Remarkably, quantification of each spot content revealed that DENV infection shifts the isoform distribution pattern of secreted α-enolase towards the basic isoforms, whereas the intracellular protein remains unaltered, suggesting that post-translational modifications might be involved in α-enolase secretion by infected cells. These findings provide new insights into the mechanisms underlying α-enolase secretion by hepatic cells and its relationship with the role of liver in dengue pathogenesis. In addition, preliminary results obtained with plasma samples from DENV-infected patients suggest an association between plasma levels of α-enolase and disease severity. Since α-enolase binds plasminogen and modulates its activation, it is plausible to speculate the association of the increase in α-enolase secretion by infected hepatic cells with the haemostatic dysfunction observed in dengue patients including the promotion of fibrinolysis and vascular permeability alterations.